Modeling and simulation of selective laser melting process - Wee, Xi Da (2015)
Selective Laser Melting (SLM) in 3D manufacturing is increasing in popularity due to the fact that it is full of potential. This technology is widely used in many industries, as there is a high possibility of creating large variety of materials, resulting in a broad range of physical and mechanical properties. As such, in this report, the author will focus on SLM process in 3D printing. The author will create a model using large-scale atomic/molecular massively parallel simulator (LAMMPS) molecular dynamics simulator so as to perform simulations of the SLM process during 3D printing. After which, the author will use the output from the LAMMPS and serve it as an input to OVITO so as to visualize and to understand how the heat from the laser is transferred across the granular powder during additive manufacturing. In addition, the author will insert another layer of granular powder and applied heat so as to simulate the actual SLM process. The results obtained from this simulation will allow the industry to have a rough idea on the thermodynamics and molecular dynamics of SLM process on granular powder. In the future, this will provide the manufacturers with a platform to conduct simulation before the real manufacturing process is conducted. This will help to increase the success rate and reduce the cost of manufacturing failure. In addition, this will also speed up the production rate of complex materials.